Respuesta :
Answer:
- (B) (x - 4)(x – 5) = 0
Step-by-step explanation:
He made a mistake at step 2.
- (x - 4)(x - 5) = 0 is incorrect as
it is same as x² - 9x + 20 = 0
It should be:
- (x - 10)(x - 2) = 0 with the end result x = 10 or x = 2
Let's solve
[tex]\\ \sf\longmapsto x^2-12x=-20[/tex]
[tex]\\ \sf\longmapsto x^2-12x+20=0[/tex]
[tex]\\ \sf\longmapsto x^2-10x-2x+20=0[/tex]
[tex]\\ \sf\longmapsto x(x-10)-2(x-20)=0[/tex]
[tex]\\ \sf\longmapsto (x-10)(x-2)=0[/tex]
[tex]\\ \sf\longmapsto x=10\:or x=2[/tex]
Option B